Thyroid disorders are common in first-degree relatives of individuals with type 1 diabetes mellitus - Araujo,Débora Batista (2015)
Objective Thyroid diseases are common in individuals with type 1 diabetes mellitus (T1DM) and should be investigated annually in these individuals. The aim of this study was to evaluate the frequency of thyroid diseases in first degree relatives (FDR) of patients with T1DM. Subjects and methods Eighty individuals (40 patients with T1DM and 40 FDR) were interviewed and blood was sampled for thyroid-stimulating hormone (TSH), free thyroxine (FT4) and thyroid peroxidase (TPO) antibodies measurement. Autoantibodies against glutamic acid decarboxylase 65 (GAD65), islet antigen-2 (IA2) and autoantibodies against insulin (AAI) were measured in FDR. Results We found a similar prevalence of thyroid dysfunction in patients with T1DM and their FDR (22.5% vs. 27.5%; p = 0,79). There were no differences in serum TSH levels (p = 0.29), FT4 (p = 0,45), frequency of abnormal TSH (p = 0.28), positive TPO antibodies (p = 0.13), titers of TPO antibodies (in positive cases) between patients with T1DM and their FDR (p = 0.94). Conclusions Thyroid abnormalities seem to be common not only in patients with T1DM but also in their FDR, which suggests that screening strategies for thyroid diseases might also be useful to these individuals.